"A Ubiquity Made Visible": Non-Sovereign Visuality, Plastic Flowers, and Labor in Cold War Hong Kong. Issue 2 (4th May 2021) - Chien, Christopher
ABSTRACT: Hong Kong's plastic flower export starting in the 1950s helped to cement U.S. transpacific supply chains as the city continued to facilitate political economic contact with the People's Republic of China (PRC) after its founding. For U.S. middle-class households, Hong Kong-made plastic flowers became a visual object that embodied race as a material force, signifying variously a fetishized "barbaric communist labor" and desirable, low-cost foreign labor. This essay examines Hong Kong's Cold War industrial history alongside Hong Kong American artist Shirley Tse's Polymathicstyrene . Tse's plastic sculpture hyper-visualizes labor as such, which may offer pathways for unsettling the state's political fetishism.